A construção de significados nas brincadeiras de faz-de-conta por crianças de uma turma de educação infantil ribeirinha da Amazônia - TEIXEIRA, Sônia Regina dos Santos (Universidade Federal do Pará, 2014)
The present study focuses the process of construction of meanings in the make-believe play for children of a riverine class in Amazon, from the formularizations of the historical and cultural psychology. In this theoretical methodological perspective, the human being constitutes itself while subject intermediated by the internalization/externalization of the meanings of its cultural group, that are constructed during the dialogical interactions. The main activity by which the preschool child affects this process is the make-believe play, for give the child opportunity to operate directly with the meanings shared in the cultural context where she lives is. In this manner, the objective of this research was to examine the dialogical interactions that happen during the make-believe play of children of a classroom of a riverine class of the Amazon to identify the meanings constructed in the interactions and to verify how, through them, the children co-construct themselves while citizens and participants of the culture. For this, I made a field-work in the classes of kindergarten of a pedagogical unit, located in the Island of the Combu, in the city of Belém of Pará, throughout the years of 2003 and 2006, that was divided in two distinct stages. At the first moment of the research, I effected the characterization of the cultural context of life of the children who frequented the classes of kindergarten. The participants of this stage were thirteen children who had frequented the classroom of kindergarten in the year of 2003, with eleven boys and two girls, between four and five years old, the teacher of the kindergarten class and the responsible ones for the children. The children and its familiar ones had been interviewed. The children had been observed playing in its houses. I analyzed the subjects, the partners, the places, objects and the meanings constructed in the kids play. At the second moment, I made the microgenetic analysis of the dialogical interactions that had occurred in the make-believe play. The participants had been sixteen children who had frequented the classroom of kindergarten in the year of 2005 and the teacher. The analyzed data showed: 1) The ways of construction of the meanings for the children and between them and the teacher; 2) The types of constructed meanings: about the world, about themselves and the others, and about the relation of themselves with the others; 3) The origin of the constructed meanings; 4) The relation culture-subjectivity. The characterization of the cultural context revealed that although they were in contact with the urban context, the children had revealed linked, mainly, to the riverine context. The microgenetic analysis of the dialogical interactions during the tricks showed that the meanings about the world, about themselves and the others, and the relation of themselves with the others, shared in the cultural context of the Island of the Combu, had been internalized, starting to constitute the subjectivities of the investigated children. It indicated in despite of make-believe play, by itself, independent of the participation of other children and the adult, contributes for the process of cultural constitution of the child, but it can be enriched with the participation of other children and the teacher, that respects the initiative, the culture, the level of development of the child and has clarity of its paper to plan and to lead the pedagogical act in one determined direction. Other children contribute increasing the motivation for the trick, including new elements of their cultural universe, renewing the subjects, offering models to be represented and creating complementation opportunities that imply in challenges to be adjusted during the interactions to the levels of developments of the partners. The teacher contributes planning interactive environment - child - child and child-teacher, respecting the activity and the level of development of the children, detaching the constructed meanings in the active and interactive way and, in some cases redirecting the play, with the purpose of the constitution of a determined type of subjectivity and not of a different one. In short, the study reveals how by means of the meanings constructed in the dialogical interactions, the children participate of their collective culture and constitute themselves as riverine people of Amazon.